2001
DOI: 10.1523/jneurosci.21-01-00340.2001
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Effects of Ethanol in DARPP-32 Knock-Out Mice

Abstract: DARPP-32 (dopamine and adenosine 3',5'-monophosphate-regulated phosphoprotein, 32 kDa) is an important component of dopaminergic function in brain areas thought to be important for drug and alcohol addiction. The present experiments characterized the acquisition of ethanol-induced conditioned taste aversion, ethanol-induced conditioned place preference, and ethanol self-administration in DARPP-32 knock-out (KO) mice compared to wild-type (WT) controls. For taste conditioning, KO and WT mice received access to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 51 publications
(75 reference statements)
7
63
0
Order By: Relevance
“…This striking result led us to investigate the motivational effects of ethanol in Ca v 2.2 null mice. We observed that Ca v 2.2 null mice developed place preference for a low dose of ethanol (1.2 gm/kg) that is not rewarding to wild-type mice but did not develop place preference to 2 gm/kg ethanol, which was rewarding to wild-type littermates and is the standard dose used in mouse ethanol place-conditioning studies (Risinger et al, 2001;Dickinson et al, 2003). In contrast, Ca V 2.2 null mice developed conditioned taste aversion when administered 2 gm/kg ethanol, although this was reduced in magnitude when compared with wild-type animals.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This striking result led us to investigate the motivational effects of ethanol in Ca v 2.2 null mice. We observed that Ca v 2.2 null mice developed place preference for a low dose of ethanol (1.2 gm/kg) that is not rewarding to wild-type mice but did not develop place preference to 2 gm/kg ethanol, which was rewarding to wild-type littermates and is the standard dose used in mouse ethanol place-conditioning studies (Risinger et al, 2001;Dickinson et al, 2003). In contrast, Ca V 2.2 null mice developed conditioned taste aversion when administered 2 gm/kg ethanol, although this was reduced in magnitude when compared with wild-type animals.…”
Section: Discussionmentioning
confidence: 89%
“…Of the total time spent in the two conditioning chambers, wild-type mice spent 57% and null mice spent 53% in the black side during the habituation session. Because the magnitude of this preference for the black side was small and was not significantly different between the two genotypes ( p ϭ 0.089; two-tailed t test), we used an unbiased protocol for conditioning (Risinger et al, 2001;Dickinson et al, 2003). Mice were conditioned to ethanol (1.2, 2.0, or 2.8 gm/kg v/v in 0.9% saline, i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, later studies have shown that the place preference can be induced to B6 mice by increasing the number of conditioning sessions with alcohol (Risinger et al, 2001;Boyce-Rustay and Risinger, 2003). Here, we used an extended protocol with six alcohol and six saline conditioning sessions, which resulted in a significant CPP in the WT animals.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of D1 receptors prevents the dephosphorylation of the NR1 subunit via a cascade that involves phosphorylation of PKA, which in turn phosphorylates dopamine and cAMP-regulated phosphoprotein-32 kDa (DARPP-32), which then inhibits the activation of PP1 phosphatase acting on the NR1 subunit [195]. Via this cascade, D1 receptor promotion of drug reinforcement, as might arise from prior exposure to drugs of abuse, reduces the sensitivity of NMDARs to blockade by ethanol [126] and may increase the motivational effects of ethanol [179].…”
Section: Consequences Of Changes In Structure Of Nmdarsmentioning
confidence: 99%